The Effect of Health Education in Dealing With Epistaxis in Children: Parents’ Knowledge and Attitude - Mikawati, Mikawati; Jafar, Alfira; Pratiwi, Rizky; ., Muaningsih; ., Suriyani (Journal of Nursing Care, 2024)
Introduction: Epistaxis itself is usually experienced by children, and the impact of children who often experience epistaxis will cause complications. Often if a child who has epistaxis whose bleeding is continuous or recurrent, usually will be immediately taken to the health unit no matter the severity of the bleeding will still cause anxiety for parents. Objective: To determine the effect of health education on the handling of epistaxis in children on the level of parent’s knowledge and outlook at PAUD Ceria Makassar.Research Methods: Using pre-experiment method with pre-post-test design approach. The sample used was 40 respondents using Accidental sampling technique. Data analysis using the Wilcoxon signed rank test. Results: Of the 40 respondents obtained pre-test results of good knowledge 14 (35%), less knowledge 26 (65%), and pre-test positive outlook 17 (42.5%), negative outlook 23 (57.5%), after health education post results of good knowledge 30 (75%) less knowledge 10 (25%), and post positive outlook 28 (70%), negative outlook 12 (30%). The test results using the Wilcoxon test showed that there was an effect of health education on the level of parental knowledge obtained a p-value of 0.000 <0.05 and the outlook of parents obtained a p-value of 0.000 <0.05. Conclusion: There is an effect of health education on the level of knowledge and outlook of parents in handling epistaxis in children.